Molecular sieves : from basic research to industrial applications : proceedings of the 3rd International Zeolite Symposium (3rd FEZA), Prague, Czech Republic, August 23-26, 2005 - Cejka, Jiri; Zilkova, N. (Nadezda); Nachtigall, P. (Petr) (Studies in surface science and catalysis, 2005)
Due to their unique porous properties, zeolites (also referred to as molecular sieves) are used in a variety of applications - major uses are in petrochemical cracking, ion-exchange (water softening and purification), and in the separation and removal of gases and solvents. Molecular Sieves: From Basic Research to Industrial Applications, Volume 158 A, B presents over 265 worldwide contributions on the latest developments in zeolitic research. Readers will find this book, which is divided into five sections: Synthesis, Characterization, Adsorption, Catalysis, and Novel applications, ideal for staying up to date on current research on porous materials. * Comprehensive overview of current research on porous materials * Contains experimental as well as theoretical input, reflecting the increasing overlap between theory and experiment * Contributions from the world's leading authorities.